2003
DOI: 10.1074/jbc.m212670200
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine Phosphorylase and 2-Deoxyribose Stimulate Human Endothelial Cell Migration by Specific Activation of the Integrins α5β1 and αVβ3

Abstract: Thymidine phosphorylase is an angiogenic factor that is frequently overexpressed in solid tumors, in rheumatoid arthritis, and in response to inflammatory cytokines. Our previous studies showed that cells expressing thymidine phosphorylase stimulated endothelial cell migration in vitro. This was a consequence of the intracellular metabolism of thymidine by thymidine phosphorylase and subsequent extracellular release of 2-deoxyribose. The mechanisms by which 2-deoxyribose might mediate thymidine phosphorylase-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
71
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 64 publications
2
71
1
Order By: Relevance
“…Cells with a high TP can secrete angiogenic factors at high levels, including the vascular endothelial growth factor (VEGF) and interleukin-8 (IL-8), but the role of sugars in the activation of these factors remains unclear [6,13]. TdR-derived sugars accumulated in the cell fractions of the membrane and cytoskeleton, which may be related to glycation of proteins by the formation of AGE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells with a high TP can secrete angiogenic factors at high levels, including the vascular endothelial growth factor (VEGF) and interleukin-8 (IL-8), but the role of sugars in the activation of these factors remains unclear [6,13]. TdR-derived sugars accumulated in the cell fractions of the membrane and cytoskeleton, which may be related to glycation of proteins by the formation of AGE.…”
Section: Discussionmentioning
confidence: 99%
“…In various in vitro studies, TP had a chemotactic effect on endothelial cells [5,6,7,8]. In vivo, TP induced angiogenesis using various cancer cell lines that were transfected with TP [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is assumed that the products of the enzyme reaction are angiogenic, in partic- ular 2-deoxy-D-ribose that is obtained by dephosphorylation of 2-deoxy-␣-D-ribose-1-phosphate. It has been proposed that the extracellular release of 2-deoxy-D-ribose forms a chemotactic gradient that mediates endothelial cell migration (25,28,29). Recent observations also suggest that 2-deoxy-D-ribose induces angiogenesis by generating oxygen radical species, which induce the secretion of oxidative stress-responsive angiogenic factors, like vascular endothelial cell growth factor, interleukin-8, and matrix metalloproteinase-1 (6,28).…”
Section: Discussionmentioning
confidence: 99%
“…These pathways could be divided into those that are focal adhesion related or growth factor related. Hotchkiss et al (25) reported that TP and D-dRib stimulate the formation of focal adhesions and activate specific integrins for endothelial cell migration. We did not observe FAK activation in our experiments.…”
Section: Discussionmentioning
confidence: 99%